Usulan Perbaikan Tata Letak Lantai Produksi PT. Porter Rekayasa Unggul untuk Meminimasi Biaya Material Handling dan Waktu Produksi dengan Metode Pairwise Exchange dan Simulasi - Arsinta Maissy Rantung; Parwadi Moengin; Sucipto Adisuwiryo (JURNAL TEKNIK INDUSTRI, 2018)
PT. Porter Superior Engineering is a manufacturing company engaged in transportation equipment. Production floor layout at PT. The Superior Engineering Porter has a work station that is not placed optimally so that the material transfer distance of the handling is far away. This affects the overall process of production, where the distance of material displacement that is not efficient affects the cost of using material handling and affects the overall production time. With the addition of the transfer time to the production carried out resulting in overload or excess production demand, so that the production target cannot be achieved in accordance with the number of orders caused by increased production time. Based on these problems, improvements are made using the Pairwise Exchange method for designing new layouts based on the minimum material handling costs and simulations as an evaluation of the proposed improvements to the new layout design. The first step in evaluating the production floor layout at PT. Superior Engineering Porters, namely by using Material Handling Check Lists and maps of the operation process. From the results of the Material Handling Check List and the map of the operating process, it is continued by designing the initial or actual production floor layout. Then design the initial production floor simulation model. After that, a verification and validation process was carried out on the design of the initial production floor simulation model. If valid, then improvements are made to the problems that exist in the production floor layout using the Pairwise Exchange method as a method to improve the existing layout based on the total minimum material transfer costs between departments. After repairs to the initial production floor layout with the results of the minimum material transfer costs, then proceed with the design of the proposed model simulation. There are three proposals on this problem. The first proposal uses the production floor layout with minimum displacement costs and the addition of material handling, the second proposal is to use the production floor layout with minimum displacement costs and the addition of machines, the third proposal is to use the production floor layout with minimum transfer costs and addition of material handling and number of machines, then selecting proposals using the bonferroni method and analysis of production so that the best proposals are obtained, namely in the second proposal with the results of units achieving production targets and minimum displacement costs 282, 61 hours and the production of 60 units in a month. Compared with the initial simulation which has a simulation time of 335.79 hours and the production of 50 units in a month.